2015
DOI: 10.1111/jch.12530
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Submaximal Endurance Training on Arterial Stiffness in Healthy Middle‐ and Long‐Distance Runners

Abstract: Measures of arterial stiffness are indicators for cardiovascular health and predictors of cardiovascular events. Arterial stiffness is responsive to acute physiologic stressors such as exercise. However, the acute effects of intensive exercise and recovery on arterial stiffness are controversial. Thirty‐seven healthy middle‐ and long‐distance runners (33 men, mean age 26.5±6.6 years) underwent evaluation of their cardiovascular stiffness at rest, after a 15‐minute warm‐up, immediately after vigorous running 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The apparent stiffening of the vessel likely involves the gradual recruitment of collagen fibers as the vessel distends with increasing arterial pressure ( 20 , 35 ). Interestingly, c quickly returned to values not different from baseline in recovery, a result in agreement with the central vascular alterations occurring in athletes during recovery, as highlighted by Müller et al ( 18 ). This may relate to a rapid arterial pressure drop concomitant to a reduction in sympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 88%
“…The apparent stiffening of the vessel likely involves the gradual recruitment of collagen fibers as the vessel distends with increasing arterial pressure ( 20 , 35 ). Interestingly, c quickly returned to values not different from baseline in recovery, a result in agreement with the central vascular alterations occurring in athletes during recovery, as highlighted by Müller et al ( 18 ). This may relate to a rapid arterial pressure drop concomitant to a reduction in sympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 88%
“…We found that higher physical fitness (expressed by marathon finishing time) was not associated with PWV kinetics after marathon (Table ). Our findings are in line with the findings of Mueller et al who could not find association between physical fitness and PWV in response to a vigorous but submaximal 3000‐m run. In summary, our results do not indicate that higher fitness levels are associated with greater reduction in PWV and, therefore, better vascular reactivity after a marathon.…”
Section: Discussionsupporting
confidence: 94%
“…That results in increased measures of arterial stiffness, like pulse wave velocity, which is an independent marker for cardiovascular events. 20,32,33 Acute effects of exercise on the vessels are a reduced arterial stiffness and lower wave reflection indices 18,34 that may represent regular adaptive responses to the demands of exercise. 18,34 However, Vlachopoulos and colleagues 18 also observed chronic changes depicted as higher pulse wave velocity in marathon runners compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…20,32,33 Acute effects of exercise on the vessels are a reduced arterial stiffness and lower wave reflection indices 18,34 that may represent regular adaptive responses to the demands of exercise. 18,34 However, Vlachopoulos and colleagues 18 also observed chronic changes depicted as higher pulse wave velocity in marathon runners compared with healthy controls. The possible explanation for chronic changes are sustained wall strain and tangential shear stress 35 caused by long lasting exercise.…”
Section: Discussionmentioning
confidence: 99%